Qing dai Chu ci xue wen xian kao shi - Chen, Xin (Zhonghua shu ju, 2022)
Zusammenfassung
國家社科基金青年項目(14CZW033). - 簡體字本. - 附錄: 清代楚辭學簡要年表
Literaturverzeichnis Seite 523-549
Keywords: Chu ci (Ancient Chinese poems) / Bibliography; Chu ci (Ancient Chinese poems); Chinese poetry / To 221 B.C. / History and criticism; Chinese poetry / Qin and Han dynasties, 221 B.C.-220 A.D. / History and criticism; Poésie chinoise / Jusqu'à 221 av. J.-C. / Histoire et critique; Poésie chinoise / 221 av. J.-C.-220 (Dynasties des Qin et des Han) / Histoire et critique; Chinese poetry; Chinese poetry / Qin and Han dynasties; Forschungsbericht